Development of synthesis protocols based on a single route to produce fullerenol with specified level of hydroxylation within practical range, and investigation of fullerenol as supercapacitor electrode additives - Chokaouychai, Sirikanya (Cranfield University, 2017)
This research aims to develop synthesis protocols (based on a single route) to produce fullerenol with specified level of hydroxylation (n(оʜ)), and to demonstrate comparison of effects from different classes of fullerenol (i.e. different n(оʜ)) in an unexplored application (energy storage). The route of fullerene hydroxylation by NaOH in presence of phase-transfer catalyst TBAH was chosen as a basis for this research. Producton consistency in terms of achieved n(оʜ) was evaluated, and effects of selected three process parameters on n(оʜ) were investigated. Non-linear relationship between amount of TBAH used and n(оʜ) showed a maximum (n(оʜ) = 14 groups) for TBAH = 24 drops, and a minimum (n(оʜ) = 8 groups) for 3 drops. Relationship between volume of NaOH solution used and n(оʜ) resembles Freundlich Adsorption Isotherm for liquid-solid adsorption. 8.0 ml NaOH solution gave the same n(оʜ) = 16 groups as 4.0 ml solution, however an increase in production capacity was more obvious. Reaction time 10-30 minutes did not cause noticeable changes to n(оʜ). Three protocols for producing three classes of fullerenol (n(оʜ)  10; n(оʜ) = 10-14; n(оʜ) = 15-20) within practical range based on TBAH-NaOH route have been developed. Adverse effects of CO₂ and O₃ on the route have been discovered. The research also established systematic mathematical calculations for determining empirical formula of fullerenol using TGA and EDX (‘TGA-EDX method’). Minimum requirements of process design for fullerenol production are provided. Scale-up syntheses using the developed protocols were conducted and the products were used for investigation on the effect of n(оʜ) on performance of symmetric activated carbon supercapacitor containing fullerenol as electrode additives. Although lower in specific capacitance (and larger ESR), all fullerenol-containing supercapacitors offered higher maximum power, energy density and charge-transfer when compared to additive-free supercapacitor - suggesting potential and possibilities of fullerenol in energy applications.
Keywords: Nanotechnology; nanomaterial; nanoparticle; fullerene; carbon; energy storage